Facile Synthesis of Anatase TiO2 Quantum‐Dot/Graphene‐Nanosheet Composites with Enhanced Electrochemical Performance for Lithium‐Ion Batteries. (17th December 2013) - Mo, Runwei; Lei, Zhengyu; Sun, Kening; Rooney, David
<x xml:space="preserve">Abstract</x> A facile method to synthesize well‐dispersed TiO2 quantum dots on graphene nanosheets (TiO2‐QDs/GNs) in a water‐in‐oil (W/O) emulsion system is reported. The TiO2/graphene composites display high performance as an anode material for lithium‐ion batteries (LIBs), such as having high reversible lithium storage capacity, high Coulombic efficiency, excellent cycling stability, and high rate capability. The excellent electrochemical performance and special structure of the composites thus offer a way to prepare novel graphene‐based electrode materials for high‐energy‐density and high‐power LIBs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>